2007
DOI: 10.1096/fj.06-7460com
|View full text |Cite
|
Sign up to set email alerts
|

The transient receptor potential vanilloid 1 (TRPV1) receptor protects against the onset of sepsis after endotoxin

Abstract: Transient potential vanilloid 1 (TRPV1) receptor is an ion channel receptor primarily localized on sensory nerves and activated by specific stimuli to initiate and amplify pain and inflammation, as typified by murine models of scald and arthritis. Little is known of the role of TRPV1 in sepsis, an infective disease associated with inflammation. Through use of a sublethal murine model of lipopolysaccharide-induced peritoneal sepsis, we provide novel evidence that genetic deletion of TRPV1 leads to an enhanced o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
82
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 39 publications
8
82
0
Order By: Relevance
“…Consistent with the cumulative evidence that points to a protective role for TRPV1 in murine sepsis models, we observe that TRPV1 activation displays a protective phenotype of reduced proinflammation, increased anti-inflammation, and downregulation of PAI-1 in toxicity and infection models of sepsis (17,27,39,40). However, in contrast to other reports on TRPV1 in sepsis, we did not detect differences in the cytokine responses of Trpv1 2/2 and WT mice treated with LPS or Pam3Cys in the absence of NADA.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent with the cumulative evidence that points to a protective role for TRPV1 in murine sepsis models, we observe that TRPV1 activation displays a protective phenotype of reduced proinflammation, increased anti-inflammation, and downregulation of PAI-1 in toxicity and infection models of sepsis (17,27,39,40). However, in contrast to other reports on TRPV1 in sepsis, we did not detect differences in the cytokine responses of Trpv1 2/2 and WT mice treated with LPS or Pam3Cys in the absence of NADA.…”
Section: Discussionsupporting
confidence: 87%
“…The majority of the in vivo work on NADA has focused on its neurologic and behavioral effects, and NADA's effects on inflammation have not been characterized (2,(35)(36)(37)(38). Although there are mixed studies suggesting that TRPV1 activation affects inflammation in models of sepsis, to our knowledge, no prior study has investigated in vivo the role of NADA or the NADA-TRPV1 axis in sepsis (17,27,39,40). Therefore, we tested the hypothesis that the administration of NADA would reduce acute systemic inflammation in sepsis via activation of TRPV1.…”
Section: T He Endogenous Lipid N-arachidonoyl Dopamine (Nada)mentioning
confidence: 99%
“…Other studies have also demonstrated that particulate matter increases intracellular Ca 2+ and induces apoptosis of cultured lung epithelial cells via activation of TRPV1 [38,99]. These results indicate that TRPV1 is a mediator of lung injury and inflammation.…”
Section: Apoptosis and Trpv1mentioning
confidence: 63%
“…However, more recently, counter-regulatory functions of TRPV1 have been described in an endotoxin-induced sepsis model in the TRPV1 knock-out mouse. In TRPV1 knock- demonstrated enhanced hypotension, hypothermia and mediator levels in peritoneal exudates, which indicated a loss of protective effects [99]. Helyes et al also investigated the role of TRPV1 in endotoxin-induced airway inflammation and subsequent bronchial hyperreactivity in TRPV1 knock-out mice using intranasal LPS administration.…”
Section: Protective Role Of Trpv1mentioning
confidence: 99%
“…At the same time, however, it has emerged that TRPV1 has important functions in homeostasis, for example, in thermoregulation. The role of TRPV1 in inflammation is under debate; several studies have demonstrated a proinflammatory effect 3,4) , while other studies have identified a protective role for TRPV1 in systemic inflammation and sepsis [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%